Renormalized non–modal theory of turbulence of plasma shear flows - Mikhailenko, V.S.; Mikhailenko, V.V.; Stepanov, K.N.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2011)
In our report, we present the results of the non-linear investigations of the temporal evolution and saturation of drift turbulence in shear flows, which have the non-modal approach as their foundation.